Functional Rhinoplasty—What Really Works?. (19th January 2023) - Mella, Jeffrey; Oyer, Samuel; Park, Stephen
Abstract : Throughout the evolution of functional rhinoplasty, numerous techniques have been described and shown to be successful. Controversy exists regarding which techniques are most effective to address various deformities. The goal of this article is to review the available literature to examine the question, which surgical techniques within functional rhinoplasty are most successful in treating nasal airway obstruction. Based on the available data, it is not currently possible to draw conclusions about the superiority of a single graft or technique in functional rhinoplasty.